Діагностика міграційних настроїв населення у регіоні (мотиваційний аспект) - Семикіна, М. В.; Кабай, В. О.; Мельнік, А. В.; Бугаєва, М. В.; Семикина, М. В.; Кабай, В. О.; Мельник, А. В.; Бугаева, М. В.; Semikina, M.; Kabay, V.; Melnik, A.; Buhaieva, M. (ЦНТУ, 2019)
Стаття присвячена аналізу специфіки мотивації міграційної поведінки українців та оцінці особливостей міграційних настроїв на регіональному рівні. Розкрито сутність понять «мотивація міграційної поведінки» та «міграційні настрої» в контексті категорій мотиваційних теорій. Висвітлено загальну оцінку міграційної ситуації в Україні та її регіонах. Здійснено діагностику міграційних настроїв населення на прикладі Кіровоградського регіону шляхом соціологічного опитування. Визначено особливості мотивації міграційної поведінки населення та базові мотиватори трудової міграції молоді. Статья посвящена анализу специфики мотивации миграционного поведения украинцев и оценке особенностей миграционных настроений на региональном уровне. Раскрыта сущность понятий «мотивация миграционного поведения» и «миграционные настроения» в контексте категорий мотивационных теорий. Представлена общая оценка миграционной ситуации в Украине и ее регионах. Осуществлена диагностика миграционных настроений населения на примере Кировоградского региона путем социологического опроса. Определены особенности мотивации миграционного поведения населения и базовые мотиваторы трудовой миграции молодежи. The article is devoted to deepening the analysis of the specifics of motivation of migration behavior of Ukrainians and assessing the characteristics of migration moods at the regional level. In recent years the migration movement of Ukrainians has become widespread. This process threatens the loss of the labor potential of the country, poses a threat to the further innovative and economic development of the state and its regions. New realities require revision of approaches to functioning of motivational mechanisms of labor migration of the population, search for acceptable ways of regulating migration behavior from the standpoint of taking into account the interests of the state and its population. At the same time, there is still a lack of constant monitoring of the migration moods of the population, study of the peculiarities and specificity of the motives of migration behavior in different regions of the country to develop effective regulatory measures. The purpose of the article is to find out the essence of "motivation of migration behavior" and "migration sentiment" and to diagnose the migration moods of the population on the example of the Kirovograd region by means of a sociological survey. Generalization of modern scientific thoughts allows us to understand labor migration as the displacement of able-bodied population to other settlements, including abroad, which is due primarily to the motives for meeting urgent and perspective socio-economic needs. Among such needs, priority is usually given to avoiding threats to life, social risks, obtaining more income from work on a temporary (once, several times, regularly) or permanent basis. In Ukraine for a long time there is a phenomenon of deformation of motivational factors that impedes the effective realization and development of accumulated human capital, adversely affects the dynamics of GDP, the state of innovation development, weakens the labor and creative activity of employees. The current situation of ineffective motivation in the sphere of labor, first of all, extremely low pay, contradicts the declared goals of building the socially oriented market economy, complicates the movement of Ukraine towards European integration. The human capital with low pay for its owners, will lose its quality. There are limited and insufficient funds for its reproduction and development. The combination of these motivational conditions and factors has the multifaceted effect on the labor choices of the population, shaping the migration moods. Thus, the emergence of migratory attitudes and the activation of migration behavior of the population is determined by the influence of a variety of objective and subjective motivational factors. These factors affect labor behavior with different strengths, in different combinations, at different economic levels. They determine the priority formation and realization of motives for moving to other settlements, including abroad. The diagnosis of migratory moods of the population on the example of a sociological survey of student youth in the Kirovograd region made it possible to establish that the basic motivator of labor migration is the size of salary with a high degree of absolute dissatisfaction with the level of own incomes. We propose to improve the internal labor market by further raising the minimum wage and taking consistent steps to shade it, as well as by introducing new approaches to quality workplace, support for self-employment and entrepreneurship. Such measures will reduce the migration sentiment of the population as a whole, and of young people in particular.
Диагностика миграционных настроений населения в регионе (мотивационный аспект)
Diagnosis of Migration Moods of the Population in the Region (Motivational Aspect)
Keywords: трудова міграція; мотивація міграційної поведінки; міграційні настрої; мотиватори; оцінка; мотиви; трудовая миграция; мотивация миграционного поведения; миграционные настроения; мотиваторы; оценка; мотивы; labor migration; motivation of migration behavior; migration moods; motivators; evaluation; motives